Detection of breath acetone by semiconductor metal oxide nanostructures-based gas sensors: A review. (October 2022) - Ahmadipour, Mohsen; Pang, Ai Ling; Ardani, Mohammad Rezaei; Pung, Swee-Yong; Ooi, Poh Choon; Hamzah, Azrul Azlan; Mohd Razip Wee, M.F.; Aniq Shazni Mohammad Haniff, Muhammad; Dee, Chang Fu; Mahmoudi, Ebrahim; Arsad, Agus; Ahmad, Muhammad Zamharir; et al.
Abstract: Diabetes mellitus (DM), an ailment caused by unregulated blood sugar levels, can lead to the failure of more than one organ in patients. Currently, blood tests are being conducted in scientific trials to analyse and track blood sugar and ketone levels. In this method, a drop of blood from a pricked finger is placed on a sensitive strip area, which is then pre-inserted into an electronic device to be analysed. However, this method is painful, invasive, and costly, which can be unsafe if not handled properly. Human breath analysis is a rapid and non-invasive approach for detecting different volatile organic compounds (VOCs), which could be indicators of various illnesses. In patients with DM, the body produces excessive amounts of ketones together with acetoacetate, β-hydroxybutyrate (BOHB), and acetone. Acetone is exhaled in the breath. It is produced when the body metabolizes fat, instead of glucose, for energy. Conventional exhalation analysis techniques are based entirely on spectrometric strategies; however, they are becoming increasingly appealing from a clinical point of view with the advancement of gas sensors. This study describes modern-day improvements to semiconductor metal oxide (SMO) gas sensors for the detection of exhaled acetone. Since 2011, all the sensor materials have been used to detect low concentrations of acetone gas (0.1 ppm–20 ppm). Several parameters that affect the performance of the sensor device are mentioned in detail, including the composite materials, morphology, doping, temperature, humidity, acetone concentration, and stability of the sensor. Finally, the applicability of the sensor is discussed. Graphical abstract: Image 1 Highlights: Sources and pathways of breath acetone and measurement techniques have been reported. A compact knowledge on the factor affecting and breath acetone sensing properties are explored. While published approaches promising, more clinical studies need to be conducted. The observed shortcomings and future prospects of breath acetone analyser are also highlighted.